Topical Amitriptyline and Ketamine in Neuropathic Pain Syndromes: An Open-Label Study - Lynch, Mary Elizabeth; Clark, Alexander John; Sawynok, Jana; Sullivan, Michael J. (The journal of pain, 2005)
Twenty eight subjects with refractory, moderate to severe peripheral neuropathic pain participated in an open label prospective trial examining perceived analgesic effect, patient satisfaction, and safety of topical amitriptyline 2%/ketamine 1% cream. Outcome measures included an 11-point numerical rating scale for pain intensity (NRS-PI), a 5-point satisfaction scale, blood chemistry screen, drug and metabolite levels, urinalyses, electrocardiogram (ECG), and physical examination. Adverse events were monitored. Twenty-one subjects completed the trial. At 6 months, subjects reported an average long-term reduction in pain of 34% (standard deviation [SD] = 37%); 5 subjects (25%) achieved 50% or greater reduction in pain and 1 subject (5%) achieved 100% reduction in pain. At 12 months, the average reduction in pain was 37% (SD = 40%); 7 subjects (40%) achieved 50% or greater pain reduction. At the end of the study, 89% of subjects rated their satisfaction as 3/5 or greater and 2 subjects (10%) were pain free. Minimal adverse events were reported and there were no serious medication related adverse events. Blood levels revealed minimal systemic absorption. In conclusion, topical 2% amitriptyline/ 1% ketamine cream was associated with long-term reduction (6-12 months) in perceived pain, moderate to complete satisfaction, and was well tolerated in treatment of neuropathic pain. There was no significant systemic absorption of amitriptyline or ketamine. This study demonstrates that topical 2% amitriptyline/1% ketamine, given over 6-12 months, is associated with long-term perceived analgesic effectiveness in treatment of neuropathic pain. Antidepressants and ketamine both produce multiple pharmacologic effects that may contribute to peripheral analgesia; such actions include block of peripheral N-methyl-D-aspartate receptors, local anesthetic properties, and interactions with adenosine systems.